Vulnerability of migrant women during disasters: a scoping review of the literature - Monica Trentin; Elena Rubini; Awsan Bahattab; Mariarosa Loddo; Francesco Della Corte; Luca Ragazzoni; Martina Valente (BMC, 2023)
Abstract Background Disasters have an unequal impact on the population because of differences in conditions of vulnerability, exposure, and capacity. Migrants and women are among the groups that are at greater risk for and disproportionately affected by disasters. However, despite the large body of evidence that analyzes their vulnerability separately, disaster research that targets migrant women is scant. The aim of this scoping review was to analyze the published scientific literature concerning the vulnerability of migrant women and the consequent negative impact they experience during disasters. Methods A literature search was conducted on December 15th, 2021 on Pubmed, Scopus, and Web of Science databases. No time filter was applied to the search. Information regarding the article's main characteristics and design, migrant women and their migration experience, as well as about the type of disaster was collected. The factors responsible for the vulnerability of migrant women and the negative outcomes experienced during a disaster were extracted and inductively clustered in main themes reflecting several vulnerability pathways. The review followed the Joanna Briggs Institute methodology for scoping reviews and relied on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Results After full text review, 14 articles met the inclusion criteria. All of them adopted a qualitative methodology and focused on COVID-19. The pandemic negatively affected migrant women, by triggering numerous drivers that increased their level of exposure and vulnerability. Overall, six vulnerability factors have been identified: legal status, poverty conditions, pre-existing health conditions, limited agency, gender inequality and language and cultural barriers. These resulted in nine impacts: worsening of mental health status, poor access to care, worsening of physical health conditions, fraud, exacerbation of poverty, gender-based violence, jeopardization of educational path, and unfulfillment of their religious needs. Conclusions This review provided an analysis of the vulnerability factors of migrant women and the pathways leading to negative outcomes during a disaster. Overall, the COVID-19 pandemic demonstrated that health equity is a goal that is still far to reach. The post-pandemic era should constitute the momentum for thoroughly addressing the social determinants of health that systematically marginalize the most vulnerable groups.